The Effect Of The Direct Method On The Reading Comprehension Ability Of Second Year Students At Sltp Advent 4 Paal Dua, Manado - Marpaung, Marlin (LPPM Universitas Advent Indonesia, 2017)
This study is to find out the reading comprehension ability of the students at SLTP Advent 4 Paal Dua Manado, when being taught using the Direct Method and the Lecture Method. The population of this study was seventy-six second year students at SLTP Advent 4 Paal Dua Manado, who were divided into two groups, the experimental and control group. The main problem of this study is to find out the effect of the Direct Method in teaching reading comprehension. The result showed that there was no difference in the reading comprehension ability of the students who are taught using Direct Method and students who are taught using Lecture Method. But there was slightly difference between the mean score of post-experimental and post-control. Therefore, the suggestion for English teachers is to teach the reading comprehension using the Direct Method because the Direct Method can improve students’ ability in reading comprehension. Key words: Reading comprehension, Direct Method.